2020
DOI: 10.1097/jcma.0000000000000438
|View full text |Cite
|
Sign up to set email alerts
|

Generation of osimertinib-resistant cells from epidermal growth factor receptor L858R/T790M mutant non-small cell lung carcinoma cell line

Abstract: Background: Lung cancer contributes to high cancer mortality worldwide with 80% of total cases diagnosed as non-small cell lung cancer (NSCLC). Epidermal growth factor receptor (EGFR) tyrosine kinase (TK) domain serves as a druggable target in NSCLC patients with exon 19 deletion and L858R mutation. However, patients eventually succumbed to resistance to first- and second-generation EGFR-TK inhibitors through activation of T790M mutation. Third-generation EGFR-TKI, Osimertinib exhibits high efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…The authors reported that osimertinib sensitivity was restored through the knockdown of IRE1α or treatment with an IRE1α inhibitor (STF-083010) [38]. The potential role of enhanced autophagy in AR against first-line osimertinib has been reported by other groups that used H1975 or PC9 models [42,53]. One study suggested that combining osimertinib with an autophagy inhibitor (CQ) could improve osimertinib cytotoxicity [42].…”
Section: Other Mechanismsmentioning
confidence: 93%
See 2 more Smart Citations
“…The authors reported that osimertinib sensitivity was restored through the knockdown of IRE1α or treatment with an IRE1α inhibitor (STF-083010) [38]. The potential role of enhanced autophagy in AR against first-line osimertinib has been reported by other groups that used H1975 or PC9 models [42,53]. One study suggested that combining osimertinib with an autophagy inhibitor (CQ) could improve osimertinib cytotoxicity [42].…”
Section: Other Mechanismsmentioning
confidence: 93%
“…The authors also reported that combining osimertinib with a TGFβR1 inhibitor (SB-431542) could overcome the osimertinib resistance mediated through this pathway [40]. Other studies that reported the involvement of EMT in acquiring resistance to first-line osimertinib used H1975 cells [13,46,53,54,[58][59][60], which were destined to develop EMT as an acquired resistance mechanism as described in our previous study [94]. Among mechanisms of EMT induction, increased ZEB1 expression [58], or decreased microRNA-200c in combination with increased ZEB1 expression [46] have been reported.…”
Section: Emtmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, when osimertinib is used to treat EGFR amplified or EGFR mutated NSCLC, such resistance evolves via: Multiple further EGFR mutations in EGFR T790M-positive NSCLC during osimertinib that increase the IC50 of osimertinib [ 15 ]; NSCLC that survives initial EGFR inhibitor treatment with either gefitinib or osimertinib, commonly do so through development of EGFR-independent activation of signal transducer and activator of transcription 3 (STAT3) and Src- YES-associated protein 1 (YAP1) signaling [ 16 , 17 ]; Transformation to squamous or small-cell lung cancer that is not dependent on EGFR for growth [ 18 ]; Evolution of parallel, growth-driving RTKs, including AXL, EGFR family members, and insulin growth factor 1 receptor, MET amplification, BRAF fusions, ALK fusions, Kras mutations and RET fusions [ 18 , 19 , 20 ]; Amplification of EGFR wild-type alleles conferring resistance to osimertinib [ 21 ], schematically depicted in Figure 1 . …”
Section: Osimertinibmentioning
confidence: 99%
“…Evolution of parallel, growth-driving RTKs, including AXL, EGFR family members, and insulin growth factor 1 receptor, MET amplification, BRAF fusions, ALK fusions, Kras mutations and RET fusions [ 18 , 19 , 20 ];…”
Section: Osimertinibmentioning
confidence: 99%